2020
DOI: 10.1111/hsc.13194
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the risk factors associated with falls in older people with diabetes receiving at‐home nursing care: Retrospective analysis of an Australian aged care provider database

Abstract: Falls among older people with diabetes mellitus (DM) are a major health concern.Preventive measures can be implemented to reduce the likelihood of falls. The aim of this study was to determine the factors most strongly associated with falls in older people living with DM who receive at-home care support services. This will inform home-visiting nurses to prioritise falls prevention strategies in the care of clients who are at high risk of falls. A retrospective analysis of routinely collected data from a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…From 27 included studies, the majority ( n = 16; 59.3%) was conducted in Europe (Adıgüzel & Acar‐Tek, 2019 ; Geurden et al, 2015 ; Johansen et al, 2015 ; Kiesswetter et al, 2020 , 2014 ; Lahmann et al, 2016 ; Leiske et al, 2015 ; Meijers et al, 2012 ; Mengelers et al, 2020 ; Neziraj et al, 2021 ; Scheepmans et al, 2017 ; Schildmeijer et al, 2018 ; Schilp et al, 2012 ; Suhr & Lahmann, 2018 ; van der Pols‐Vijlbrief et al, 2016 ; Vikman et al, 2011 ). The others were conducted in Australia (Brett et al, 2020 ; Burton et al, 2018 ; Meyer et al, 2020 ; Rist et al, 2012 ), Canada (Doran et al, 2013 ; Northwood et al, 2021 ), Brazil (da Silva Gabriel Capeletto et al, 2021 ; Rocha do Carmo et al, 2020 ) and China (Xu et al, 2018 ). Two studies were systematic reviews which included samples from Europe, Asia, America, Australia and Africa (Cereda et al, 2016 ) and Europe, Asia and America (Scheepmans et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 27 included studies, the majority ( n = 16; 59.3%) was conducted in Europe (Adıgüzel & Acar‐Tek, 2019 ; Geurden et al, 2015 ; Johansen et al, 2015 ; Kiesswetter et al, 2020 , 2014 ; Lahmann et al, 2016 ; Leiske et al, 2015 ; Meijers et al, 2012 ; Mengelers et al, 2020 ; Neziraj et al, 2021 ; Scheepmans et al, 2017 ; Schildmeijer et al, 2018 ; Schilp et al, 2012 ; Suhr & Lahmann, 2018 ; van der Pols‐Vijlbrief et al, 2016 ; Vikman et al, 2011 ). The others were conducted in Australia (Brett et al, 2020 ; Burton et al, 2018 ; Meyer et al, 2020 ; Rist et al, 2012 ), Canada (Doran et al, 2013 ; Northwood et al, 2021 ), Brazil (da Silva Gabriel Capeletto et al, 2021 ; Rocha do Carmo et al, 2020 ) and China (Xu et al, 2018 ). Two studies were systematic reviews which included samples from Europe, Asia, America, Australia and Africa (Cereda et al, 2016 ) and Europe, Asia and America (Scheepmans et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, the six nursing‐sensitive indicators of falls, incontinence, malnutrition, pain, pressure injury and restraints were reported 34 times in the 27 included studies. The most frequently measured indicator in HC was malnutrition ( n = 11; Adıgüzel & Acar‐Tek, 2019 ; Cereda et al, 2016 ; Geurden et al, 2015 ; Kiesswetter et al, 2014 , 2020 ; Lahmann et al, 2016 ; Meijers et al, 2012 ; Neziraj et al, 2021 ; Rist et al, 2012 ; Schilp et al, 2012 ; van der Pols‐Vijlbrief et al, 2016 ), followed by falls ( n = 9) (Brett et al, 2020 ; Burton et al, 2018 ; Doran et al, 2013 ; Meijers et al, 2012 ; Meyer et al, 2020 ; Neziraj et al, 2021 ; Rocha do Carmo et al, 2020 ; Schildmeijer et al, 2018 ; Vikman et al, 2011 ). Prevalence and incidences regarding restraints (da Silva Gabriel Capeletto et al, 2021 ; Mengelers et al, 2020 ; Scheepmans et al, 2017 , 2018 ) and pressure injury (Doran et al, 2013 ; Johansen et al, 2015 ; Neziraj et al, 2021 ; Schildmeijer et al, 2018 ) were reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings align with previous studies reporting intrinsic fall risk factors, such as dizziness, diseases, alcohol, medications, and nutrition deficiencies. 9,10,13,43 In addition, behavioral factors have been reported. 9 The fact that the person was living alone also appeared to be a risk factor for accidents in some cases.…”
Section: Discussionmentioning
confidence: 99%